Paralinguistic Perception in Interpersonal Communication Among Blind Individuals: A Conceptual Review of The Role of Vocal Tone - Winda Puji Lestari (Jurnal Ilmiah Multidisiplin, 2026)
Interpersonal communication among blind individuals relies heavily on auditory information because visual cues such as facial expressions, eye contact, and body language are inaccessible. Consequently, paralinguistic cues, particularly vocal tone, become the primary means of interpreting communicative intentions and emotions. This study aims to conceptually examine the role of paralinguistic perception in interpersonal communication among blind individuals through a narrative literature review. Relevant literature from communication studies, psychology, neuroscience, and disability studies was synthesized using a qualitative conceptual approach to explain the relationship between auditory compensation, vocal perception, and pragmatic interpretation. The findings indicate that cross-modal neuroplasticity enhances auditory sensitivity, enabling blind individuals to perceive subtle vocal variations. However, communication misunderstandings may still occur when vocal tone is inconsistent with the speaker's intended meaning because visual confirmation is unavailable. This study proposes an interdisciplinary conceptual framework demonstrating how visual impairment, auditory compensation, paralinguistic perception, and pragmatic interpretation collectively influence interpersonal communication. The findings provide theoretical contributions to communication studies and practical implications for promoting more inclusive and effective communication with blind individuals.